The Development of Digital Teaching to Improve the Quality of Student Learning in the Revolution 4.0 Era at Warmadewa University - I Wayan Parwata; Suwarni; Ahmad Hariyadi; Zulkarnaini; Mochamad Heru Riza Chakim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
To complete the answers to the research on the topic of producing digital learning to enhance the quality of student learning in the technological revolution 4.0 era at the University of Warmadewa, the researchers have gathered various materials that respond to research questions. Similarly, to collect primary data, the researchers interviewed 30 academics (students and lecturers) at the University of Warmadewa to learn about their perspectives and experiences in developing digital-based teaching to improve student learning outcomes during regular and throughout education. Hence, it reviewed different data sets, both in the form of secondary source data from various publications connected to Technology and instruction and data that the researchers questioned academics to find answers to. The researchers could simplify the development of digital teaching to improve the quality of student learning in the Revolution 4.0 era at Warmadewa University. It has resulted several new understandings, such as Technology has innovated the learning process as the digital application have helped academics in solving learning challenge and bring more benefits. It hopes these findings bring new insights into learning in higher education and policy-making uses. Keywords: Development Digital Teaching, Improving Students’ Quality, Learning Revolution